2022
DOI: 10.3390/nano12213893
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Wafer CMP Slurry Using a Hydrolysis Reaction Accelerator with an Amine Functional Group Remarkably Enhances Polishing Rate

Abstract: Recently, as an alternative solution for overcoming the scaling-down limitations of logic devices with design length of less than 3 nm and enhancing DRAM operation performance, 3D heterogeneous packaging technology has been intensively researched, essentially requiring Si wafer polishing at a very high Si polishing rate (500 nm/min) by accelerating the degree of the hydrolysis reaction (i.e., Si-O-H) on the polished Si wafer surface during CMP. Unlike conventional hydrolysis reaction accelerators (i.e., sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The pH of the polishing solution exerts a significant influence on the performance and characterization outcomes of wafer polishing. In this paper, a pH of 10.5 was selected as the base condition, based on previous findings and the literature [21,22]. It was demonstrated that the addition of surfactants employed in this study does not affect the pH of the polishing solution.…”
Section: Introductionmentioning
confidence: 98%
“…The pH of the polishing solution exerts a significant influence on the performance and characterization outcomes of wafer polishing. In this paper, a pH of 10.5 was selected as the base condition, based on previous findings and the literature [21,22]. It was demonstrated that the addition of surfactants employed in this study does not affect the pH of the polishing solution.…”
Section: Introductionmentioning
confidence: 98%
“…Polyamines are a representative class of amine additives that can achieve large MRR improvements. Beo et al [ 23 ] achieved an MRR of up to 552.8 nm/min using polyamines in the Si CMP process, which is three times higher than the MRR of conventional metallic alkalis such as KOH and NaOH. Researchers have investigated the role of polyamines in Si CMP using X-ray photoelectron spectroscopy (XPS) and contact angle testing [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beo et al [ 23 ] achieved an MRR of up to 552.8 nm/min using polyamines in the Si CMP process, which is three times higher than the MRR of conventional metallic alkalis such as KOH and NaOH. Researchers have investigated the role of polyamines in Si CMP using X-ray photoelectron spectroscopy (XPS) and contact angle testing [ 23 , 24 ]. They discovered that polyamine chemically reacts with the silicon surface to form Si–N bonds, and that it can effectively reduce the contact angle of slurry on the silicon surface.…”
Section: Introductionmentioning
confidence: 99%